Indian system of medicine used concurrently with standard conventional medicine improves quality of life in patients of cardio vascular diseases (C.V.D) (Indian Journal of Traditional Knowledge (IJTK), 2023)
Worldwide there is increased shift towards usage of traditional medicine in patients of chronic diseases like CardioVascular Disorders. In India, these medicines are used concurrently. Objective of the study was to ascertain prevalence andeffect of concurrent traditional drug therapy with standard pharmacotherapy in patients with CVD. The present study used across sectional study design to assess the prevalence and a prospective cohort design to assess the effect of concurrentAyurvedic medicines with standard pharmacotherapy in terms of quality of life. After screening 600 patients, 128 werefound taking such medicines. Out of these, 100 were recruited as cases (Group-I), while 100 who were matched in terms ofage, body mass index, ejection fraction, and receiving standard therapy only were recruited as controls (Group-II).Assessment parameters included demographic, biochemical, ejection fraction through echocardiography, distance covered insix Minute walk Test (6MWT), Quality of Life (QOL) through Kansas City Cardio-myopathy Questionnaire (KCCQ) andSeattle Angina Questionnaire (SAQ) with follow up at 6 months. Prakriti as mentioned in Ayurveda was also assessed usinga questionnaire. Both groups were comparable at base line. Total 87 in Group-I and 91 in Group-II completed the study.Further, 76% patients were diagnosed with heart failure (HF) and 24% with coronary artery disease (CAD). There was nochange in distance covered in 6MWT in both HF or CAD groups. But there was improvement in all cases in domains ofKCCQ and SAQ as compared to controls. To conclude, concurrent use of traditional medicine with standard conventionalcare in CVD may improve quality of life in cardiovascular disorders.